What are the advantages of using leftover cooking oil waste as an aromatherapy candle to prevent pollution? - Putra, Fredi Ganda; Sari, Adinda Puspita; Qurotunnisa , Asri; Rukmana , Astari; Darmayanti, Rani; Choirudin, Choirudin (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2023)
The increase in used cooking oil refuse contributes to environmental degradation. A lack of public comprehension and cognizance of waste management also contributes to this. If these actions persist, the water quality will deteriorate, and natural disasters may occur. Every resident of the village of Russia, which encompasses 12,00 km2, generates used cooking oil refuse. As part of the Serumpun Melayu Real Work Lecture (KKN) service activities, used cooking oil is recycled into aromatherapy candles in order to prevent impacts that will harm people's health as well as pollution of ecotourism spots around Rusaba village and to raise awareness about waste processing. On Thursday, August 24, 2023, the service activity occurred in the Rusaba village community hall, Punduh Pedada subdistrict, Peshawar district. Service activities are carried out using socialization and training methods, including conducting surveys and observations, preparing for socialization by coordinating with the village, carrying out socialization activities with material presented through presentations and direct practice, and evaluating activities through questions and responses. Participants considering the socialization activities carried out The implementation of socialization activities for creating aromatherapy candles from used cooking oil waste has proven effective and can be used to increase the number of micro, small, and medium-sized enterprises (MSMEs) owned by homemakers.